Analisis Profil Kompetensi Literasi Sains Siswa SMA Pada Materi Inti Atom dan Radioaktivitas - Wardi, Ladika Zuhrotul; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Universitas Negeri Surabaya, 2023)
The level of scientific literacy among Indonesian students is low and continues to decline every year. This can be caused by several things related to the learning process at school. The purpose of this study is to describe the profile of high school students' scientific literacy competence in atomic nucleus and radioactivity materials. The competency indicators analyzed refer to PISA 2018, namely: a) Explain phenomena scientifically, b) Evaluate and design scientific investigations, and c) Interpret data and evidence scientifically. This research is a quantitative approach with descriptive analysis method. The research was conducted in May 2023 in the even semester of the 2022/2023 academic year in one of the public high schools in Gresik Regency. The population in this study were 2 classes, namely XII IPA 4 and XII IPA 5, totaling 72 students. The sampling technique used random sampling taken from each class randomly with a total of 50 students. The instrument used was a science literacy test developed with a valid category and a reliability value of 0.492. The results of this study are the profile of students' science literacy competence obtained by 6% very low, 44% low, 14% sufficient, 30% high, and 6% very high. As for the average value of each indicator of scientific literacy competence, the average score is 67.6 with a high category for indicators explaining scientific phenomena, an average score of 50.8 with a low category for indicators evaluating and designing scientific investigations, an average score of 45.88 with a low category for indicators interpreting data and evidence scientifically. So that the overall average ability of students' scientific literacy competencies is categorized as sufficient. Keywords : Student profile, Scientific literacy, Atomic nucleus and radioactivity